From the court to the classroom, and from the classroom to the court: Likes, dislikes, and rites of passage between criminal justice and teaching (Delito y Sociedad, 2023)
This article seeks to analyze the functioning of the judicial institution based on some representations offered by actors who work in criminal justice and also carry out teaching activities. Specifically, we explore what these actors like and dislike about the judicial institution itself together with the intersections that are generated between the courts and the classrooms in which they dictate content related to law.
Keywords: criminal justice, teaching, liking